Production and quality of watermelon fruits (Citrullus lanatus) in response to different sources of fertilization - Jhonata Lemos da Silva; Melk Leite Santana; Chayane Lemos da Silva (Acta Biológica Catarinense, 2022)
The objective of this work was to evaluate the production and quality of watermelon fruits in response to different sources of fertilization in the municipality of Humaitá (AM). The experimental design used was a randomized block design with three replications. The treatments were: T1 – without fertilization (control), T2 – 20 ton. ha-1 of cattle manure, T3 – 10 ton.ha-1 of vegetable ashes, T4 – 10 ton.ha-1 chicken manure, T5 – 10 ton.ha-1 of açaí kernels and T6 – liming and mineral fertilizer with NPK. Fruit quality and yield attributes were evaluated, such as number of fruits, yield, total soluble solids (°Brix) and titratable acidity. All treatments differed statistically in yield and quality, in relation to soil without fertilization. The T6 treatment provided higher productivity and higher levels of total soluble solids of commercial fruits. It was demonstrated that the type of fertilizer, if used in the right way, can improve the general quality of watermelon fruits and improve the crop’s production system. In the cultivation of watermelon, several sources of organic fertilizer can be used, such as manure from cattle, sheep, goats or poultry, which recommends future tests with supplementation of mineral fertilizer.